Positive electrode active material, in-situ electrochemical modification method and application
Through in-situ electrochemical modification method, the use of ferrocene hexafluorophosphate to form a stable protective layer and doped Fe ions in lithium-ion batteries, solving the problem of poor cycling performance of LiNi0.5Mn1.5O4 material under high current density. , improving the energy density and cycle stability of lithium-ion batteries.
Patent Information
- Application Number
- CN202411415234.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2044-10-11
AI Technical Summary
The spinel phase positive electrode active material LiNi0.5Mn1.5O4 has poor cycling performance under large current density, mainly because the instability of its contact interface with the electrolyte leads to the decomposition of the electrolyte and the deterioration of the material structure.
By using in-situ electrochemical modification method, the electrolyte of LiNi0.5Mn1.5O4 and ferrocene hexafluorophosphate are assembled, and the charge and discharge cycle is carried out to form a stable protective layer and doped Fe ions, which enhances the structural stability of the material. Inhibits the dissolution and structural degradation of Mn.
The structural stability and cycling performance of LiNi0.5Mn1.5O4 are significantly improved, and the performance of lithium-ion batteries with high energy density and long cycle life is achieved.
Smart Images

Figure CN119324223A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of positive electrode materials, and in particular to a positive electrode active material and an in-situ electrochemical modification method and application. Background Art
[0002] With the continuous and rapid development of fields such as portable electronic devices and electric vehicles, lithium-ion batteries, as the most widely used energy storage solution, are subject to increasingly stringent performance requirements. In lithium-ion batteries, the positive electrode active material is one of the core components that determine its performance. The choice of positive electrode material directly affects key parameters such as the battery's energy density, cycle stability, and charge and discharge rate.
[0003] The positive electrode active material of lithium-ion batteries generally refers to a substance that can conduct electrons and transport ions during the insertion / extraction process of lithium ions. The positive electrode materials widely studied and applied at present include oxides, phosphates and silicon-based compounds. Among them, spinel structure materials such as LiNi 0.5 Mn 1.5 O4 has attracted much attention due to its excellent properties.
[0004] LiNi 0.5 Mn 1.5 O4 is a positive electrode active material with a spinel phase structure, composed of nickel, manganese and oxygen, and its chemical formula is LiNi 0.5 Mn 1.5 O4. This material is favored for its high operating voltage platform (about 4.7V vs.Li) and high energy density (about 650Wh / kg) in lithium-ion batteries. The high operating voltage platform means that it can provide higher battery voltage, thereby achieving higher energy density and longer battery life, which is particularly important for electric vehicles and large-capacity electronic devices.
[0005] However, despite the LiNi 0.5 Mn 1.5 O4 has these significant advantages, but the current spinel phase positive electrode active material LiNi 0.5 Mn 1.5 The cycling performance of O4, especially the cycling performance at higher current density, is poor, mainly due to the fact that LiNi 0.5 Mn 1.5 The extreme instability of the contact interface between the O4 positive electrode and the electrolyte causes the decomposition of the electrolyte, the dissolution of Mn in the material, and the 3+ Structural degradation caused by the Jahn-Teller distortion effect.
[0006] Based on this, the development of LiNi 0.5 Mn 1.5O4 modified materials and methods to solve the above problems. Summary of the invention
[0007] The purpose of the present invention is to overcome the LiNi 0.5 Mn 1.5 The defect of O4 is poor cycling performance at higher current density.
[0008] A first aspect of the present invention is:
[0009] Provided is an in-situ electrochemical modification method for a positive electrode active material.
[0010] A second aspect of the present invention is:
[0011] A positive electrode active material is provided.
[0012] The third aspect of the present invention is:
[0013] A lithium ion battery is provided.
[0014] Specifically, the technical solution adopted according to the first aspect of the present invention is:
[0015] An in-situ electrochemical modification method for a positive electrode active material comprises the following steps:
[0016] LiNi 0.5 Mn 1.5 O4 is used as a positive electrode active material to prepare a slurry, and the slurry is coated on a metal foil and dried to obtain a positive electrode sheet;
[0017] The positive electrode sheet, the electrolyte containing ferrocene hexafluorophosphate and the negative electrode are assembled into a battery, and the in-situ electrochemical modification of the positive electrode active material is completed through charge and discharge cycles.
[0018] According to the embodiments of the present invention, one of the technical solutions has at least one of the following advantages or beneficial effects:
[0019] In the method of the present invention, when LiNi 0.5 Mn 1.5 When the positive electrode of O4 begins to charge and discharge, during the charging process, the Mn 3+ A disproportionation reaction will occur, and part of it will form Mn 4+ Remain in the lattice, and part of it will form Mn 2+ Dissolved in the electrolyte, due to the lack of Mn, vacancies appear in the material lattice; during the discharge process, ferrocene hexafluorophosphate (C 10 H 10 F6P 10) The additive will decompose before the solvent molecules, and can simultaneously optimize the composition of the positive electrode interface CEI film and the negative electrode interface SEI film to form a stable protective layer, alleviate the side reactions at the contact interface between the positive electrode material surface and the electrolyte, and inhibit the dissolution of Mn.
[0020] In addition, ferrocene hexafluorophosphate (C 10 H 10 F6P 10 The Fe ions released by the additive will enter the Mn vacancies and support the LiNi 0.5 Mn 1.5 The crystal framework of O4 enhances its structural stability and reduces the Jahn-Teller distortion effect, reducing structural degradation.
[0021] After the above microscopic process, LiNi 0.5 Mn 1.5 A stable CEI film is formed on the surface of O4, and an appropriate amount of Fe ions are uniformly doped into the bulk phase. Therefore, the LiNi 0.5 Mn 1.5 O4 crystal structure strength and structural stability during the cycle.
[0022] The method of the present invention completes the in-situ electrochemical modification during the charge and discharge cycle. The charge and discharge cycle process of the battery is the modification process of the CEI film and the doping process of Fe ions. 0.5 Mn 1.5 The modification of O4 material is very thorough and the process is simple. The modification method provided by the present invention is simple, easy to operate, low in cost and suitable for large-scale commercial production. The prepared modified LiNi 0.5 Mn 1.5 O4 has excellent structural stability, long cycle stability at high current density and high capacity retention. This method is used to modify LiNi 0.5 Mn 1.5 O4 active materials can enable lithium-ion batteries to have ultra-high energy density, excellent cycle performance at high current density and long service life.
[0023] According to one embodiment of the present invention, the concentration of ferrocene hexafluorophosphate in the electrolyte containing ferrocene hexafluorophosphate is 0.0001M to 0.0005M. Since ferrocene hexafluorophosphate provides an Fe source, too little ferrocene hexafluorophosphate will result in a small amount of doping elements in the subsequent doping process, and the LiNi 0.5 Mn 1.5The lattice vacancies generated by the dissolution of Mn in the O4 material cause the crystal structure to still degenerate, so that the improvement of the cycle performance of lithium nickel manganese oxide at high voltage is not obvious; and too much ferrocene hexafluorophosphate will increase the thickness of the CEI film, and the unconsumed ferrocene hexafluorophosphate still exists in the electrolyte, which may have an adverse effect on the battery performance; therefore, an appropriate amount of ferrocene hexafluorophosphate can make the amount of doping elements in the subsequent doping process more moderate, without changing the LiNi 0.5 Mn 1.5 While improving the crystal structure and electrochemical properties of O4 positive electrode materials, its structural stability and electrochemical performance are also improved.
[0024] According to one embodiment of the present invention, the metal foil comprises Al foil.
[0025] According to one embodiment of the present invention, the charge and discharge cycle comprises the following steps: first charging to 4.9-5.0V at a rate of 0.1C-0.3C, then discharging to 3.5-3.6V at the same rate, and after 3-5 charge and discharge cycles, an in-situ electrochemically modified positive electrode active material is obtained.
[0026] According to one embodiment of the present invention, during the charge-discharge cycle, the number of charge-discharge cycles is 3 to 5 times (preferably 5 times) at a relatively low rate (0.1C to 0.3C rate), which can ensure the formation of the CEI film and the complete doping of Fe ions into the LiNi 0.5 Mn 1.5 The Mn vacancies in the O4 lattice are conducive to the subsequent high-rate cycling process, making the cycling performance of the in-situ electrochemically modified lithium nickel manganese oxide more significantly improved. When the rate is not within the range of 0.1C to 0.3C during the charge and discharge cycle, Fe ions cannot be doped into or cannot be completely doped into LiNi 0.5 Mn 1.5 In the Mn vacancies of the O4 lattice.
[0027] According to an embodiment of the present invention, when the charge and discharge cycle is performed at a lower rate, the rate is 0.1C to 0.2C.
[0028] According to an embodiment of the present invention, when the charge and discharge cycle is performed at a lower rate, the rate is 0.2C to 0.3C.
[0029] According to one embodiment of the present invention, in the process of preparing the slurry, positive electrode active material, conductive agent and binder are also used, and the mass ratio of the positive electrode active material, conductive agent and binder is 7-9:2-3:1.
[0030] According to one embodiment of the present invention, the thickness of the slurry layer is 50 to 200 μm. A too thick slurry layer requires too long activation time, that is, more charge and discharge cycles are required to complete the in-situ electrochemical modification process. In addition, more ferrocene hexafluorophosphate additives are required to complete uniform doping, thereby increasing production costs.
[0031] According to one embodiment of the present invention, the conductive agent includes conductive carbon black (SP).
[0032] According to one embodiment of the present invention, the adhesive comprises polyvinylidene fluoride (PVDF).
[0033] According to one embodiment of the present invention, the drying is a two-step drying process, wherein the first step of drying is to dry the metal foil coated with the slurry at 80°C to 110°C under normal pressure, and the second step of drying is to dry the metal foil under vacuum at 80°C to 110°C.
[0034] According to one embodiment of the present invention, the first step of drying includes drying in an air drying oven.
[0035] According to one embodiment of the present invention, the second step of drying is a vacuum drying process.
[0036] According to an embodiment of the present invention, the ratio of the time of the first step drying to the time of the second step drying is 1 to 4 hours: 8 to 12 hours.
[0037] Reasonable drying temperature and drying time are conducive to the complete evaporation of the solvent in the slurry.
[0038] According to one embodiment of the present invention, the components of the electrolyte include: ferrocene hexafluorophosphate, lithium hexafluorophosphate and a solvent.
[0039] According to one embodiment of the present invention, the solvent of the electrolyte includes ethyl carbonate EC and methylene carbonate EMC, wherein the volume ratio of EC to EMC is 3-4:7-8.
[0040] According to one embodiment of the present invention, the preparation of the electrolyte includes the following steps: mixing ferrocene hexafluorophosphate, lithium hexafluorophosphate and a solvent, and stirring to obtain the electrolyte.
[0041] According to one embodiment of the present invention, during the preparation of the electrolyte, the temperature is maintained at room temperature (about 25°C) during stirring, the stirring time is 10 to 12 hours, and the speed is 650-680 r / min. The stirring time is preferably 12 hours. A reasonable stirring time is beneficial to the ferrocene hexafluorophosphate (C 10 H 10 F6P 10 ) is fully dissolved.
[0042] According to one embodiment of the present invention, LiNi 0.5 Mn 1.5 After O4 as the positive electrode active material is mixed with a conductive agent, a binder and a solvent, a stirring step is also included. The stirring temperature is room temperature (about 25° C.), the stirring time is 0.5 to 2 hours, and the rotation speed is 650-680 r / min.
[0043] According to one embodiment of the present invention, the material of the negative electrode includes a lithium-containing material.
[0044] According to one embodiment of the present invention, the lithium-containing material comprises a lithium sheet.
[0045] According to one embodiment of the present invention, the positive electrode plate, the electrolyte containing ferrocene hexafluorophosphate and the negative electrode are assembled into a battery, and the battery is a half-cell.
[0046] According to one embodiment of the present invention, the half-cell is a 2032 type button cell.
[0047] Specifically, the technical solution adopted according to the second aspect of the present invention is:
[0048] A positive electrode active material is prepared by the method.
[0049] Specifically, the technical solution adopted according to the third aspect of the present invention is:
[0050] A lithium ion battery comprises the positive electrode active material.
[0051] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0053] Figure 1 This is an optical photograph of the modified electrolyte prepared in Example 1 with a ferrocene hexafluorophosphate concentration of 0.0002 M.
[0054] Figure 2 The unmodified LiNi used in Example 1 0.5 Mn 1.5 XRD spectrum of O4.
[0055] Figure 3 The unmodified LiNi used in Example 1 0.5 Mn1.5 SEM image of O4.
[0056] Figure 4 The unmodified LiNi used in this Example 1 0.5 Mn 1.5 TEM image of O4.
[0057] Figure 5 The unmodified LiNi used in Example 1 0.5 Mn 1.5 Element distribution picture of O4 material.
[0058] Figure 6 The graph is a cycle performance curve of the lithium ion batteries prepared in Example 1 and Comparative Example 3.
[0059] Figure 7 The figure is a rate performance diagram of the lithium ion batteries prepared in Example 1 and Comparative Example 3.
[0060] Figure 8 For LiNi in Example 1 0.5 Mn 1.5 TEM images of O4 cathode before and after modification.
[0061] Fig. 9 For LiNi in Example 1 0.5 Mn 1.5 TOF-SIMS images of O4 positive electrode before and after modification.
[0062] Fig.10 The LiNi modified by battery cycle in Example 1 0.5 Mn 1.5 Element distribution picture of O4 positive electrode.
[0063] Fig.11 The LiNi modified by battery cycle in Example 1 0.5 Mn 1.5 XPS etching image of Fe element of O4 positive electrode.
[0064] Fig.12 The cycle performance curves of the lithium-ion batteries prepared in Example 1 and Comparative Example 1 are shown.
[0065] Fig.13 The cycle performance curves of the lithium-ion batteries prepared in Example 1 and Comparative Example 2 are shown. DETAILED DESCRIPTION
[0066] In the description of the present invention, if there is a description of first, second, etc., it is only for the purpose of distinguishing technical features, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.
[0067] The words "preferably", "more preferably", etc. in the present invention refer to embodiments of the present invention that may provide certain beneficial effects in certain circumstances. However, other embodiments may also be preferred under the same circumstances or other circumstances. In addition, the description of one or more preferred embodiments does not imply that other embodiments are not applicable, nor is it intended to exclude other embodiments from the scope of the present invention.
[0068] When a numerical range is disclosed herein, the above range is considered to be continuous and includes the minimum and maximum values of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0069] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of the present invention.
[0070] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0071] Example 1
[0072] An in-situ electrochemical modification method for a positive electrode active material comprises the following steps:
[0073] S1: Accurately weigh 0.00133 g of ferrocene hexafluorophosphate (C 10 H 10 F6P 10 ) was added into 20 mL of a common high-voltage electrolyte without any additives (components: 1.2 M LiPF6 + EC: EMC (v:v = 3:7)) to obtain a modified electrolyte with a ferrocene hexafluorophosphate concentration of 0.0002 M, and stirred at room temperature (about 25°C) for 12 h to completely dissolve it;
[0074] S2: 0.21g of ordinary LiNi without any modification 0.5 Mn 1.5O4 was mixed with 0.06 g of conductive agent (carbon black SP), 0.6 g of binder (polyvinylidene fluoride PVDF, 5 wt%), and 0.4 g of solvent (N-methylpyrrolidone) as the positive electrode active material, and stirred at room temperature (about 25 ° C) for 2 h to obtain a slurry. The slurry was coated on an Al foil with a 50 μm scraper, and then the coated Al foil was dried in a 110 ° C blast drying oven for 4 h, and then transferred to a vacuum drying oven at 110 ° C for 12 h to obtain LiNi 0.5 Mn 1.5 O4 positive electrode;
[0075] S3: Assemble a half-cell with the lithium sheet as the negative electrode for charge and discharge cycles. First, charge to 4.9V at a rate of 0.2C, then discharge to 3.5V at a rate of 0.2C, and repeat the charge and discharge cycle 5 times at a rate of 0.2C to obtain an in-situ electrochemically modified positive electrode active material, thereby completing the in-situ electrochemical modification of the positive electrode active material.
[0076] Example 2
[0077] The difference between Example 2 and Example 1 is that in step S1, the concentration of ferrocene hexafluorophosphate in the modified electrolyte is different. The concentration of ferrocene hexafluorophosphate in Example 1 is 0.0002M, and the concentration of ferrocene hexafluorophosphate in Example 2 is 0.0003M.
[0078] Specific:
[0079] An in-situ electrochemical modification method for a positive electrode active material comprises the following steps:
[0080] S1: Ferrocene hexafluorophosphate (C 10 H 10 F6P 10 ) was added into 20 mL of a common high-voltage electrolyte without any additives (components: 1.2 M LiPF6 + EC: EMC (v:v = 3:7)) to obtain a modified electrolyte with a ferrocene hexafluorophosphate concentration of 0.0003 M, and stirred at room temperature (about 25°C) for 12 h to completely dissolve it;
[0081] S2: 0.21g of ordinary LiNi without any modification 0.5 Mn 1.5 O4 was mixed with 0.06 g of conductive agent (carbon black SP), 0.6 g of binder (polyvinylidene fluoride PVDF, 5 wt%), and 0.4 g of solvent (N-methylpyrrolidone) as the positive electrode active material, and stirred at room temperature (about 25 ° C) for 2 h to obtain a slurry. The slurry was coated on an Al foil with a 50 μm scraper, and then the coated Al foil was dried in a 110 ° C blast drying oven for 4 h, and then transferred to a vacuum drying oven at 110 ° C for 12 h to obtain LiNi0.5 Mn 1.5 O4 positive electrode;
[0082] S3: Assemble a half-cell with the lithium sheet as the negative electrode for charge and discharge cycles. First, charge to 4.9V at a rate of 0.2C, then discharge to 3.5V at a rate of 0.2C, and repeat the charge and discharge cycle 5 times at a rate of 0.2C to obtain an in-situ electrochemically modified positive electrode active material, thereby completing the in-situ electrochemical modification of the positive electrode active material.
[0083] Comparative Example 1
[0084] The difference between Comparative Example 1 and Example 1 is that in Comparative Example 1, ferrocene hexafluorophosphate is replaced by ferrocene.
[0085] Specific:
[0086] An in-situ electrochemical modification method for a positive electrode active material comprises the following steps:
[0087] S1: Add ferrocene to 20 mL of a common high-voltage electrolyte without any additives (components: 1.2 M LiPF6 + EC: EMC (v:v = 3:7)) to obtain a modified electrolyte with a ferrocene concentration of 0.0002 M, and stir at room temperature (about 25°C) for 12 h to completely dissolve it;
[0088] S2: 0.21g of ordinary LiNi without any modification 0.5 Mn 1.5 O4 was mixed with 0.06 g of conductive agent (carbon black SP), 0.6 g of binder (polyvinylidene fluoride PVDF, 5 wt%), and 0.4 g of solvent (N-methylpyrrolidone) as the positive electrode active material, and stirred at room temperature (about 25 ° C) for 2 h to obtain a slurry. The slurry was coated on an Al foil with a 50 μm scraper, and then the coated Al foil was dried in a 110 ° C blast drying oven for 4 h, and then transferred to a vacuum drying oven at 110 ° C for 12 h to obtain LiNi 0.5 Mn 1.5 O4 positive electrode;
[0089] S3: Assemble a half-cell with the lithium sheet as the negative electrode for charge and discharge cycles. First, charge to 4.9V at a rate of 0.2C, then discharge to 3.5V at a rate of 0.2C, and repeat the charge and discharge cycle 5 times at a rate of 0.2C to obtain an in-situ electrochemically modified positive electrode active material, thereby completing the in-situ electrochemical modification of the positive electrode active material.
[0090] Comparative Example 2
[0091] The difference between Comparative Example 2 and Example 1 is that in Comparative Example 2, ferrocene hexafluorophosphate is replaced by ferrocene tetrafluoroborate.
[0092] Specific:
[0093] An in-situ electrochemical modification method for a positive electrode active material comprises the following steps:
[0094] S1: Add ferrocene tetrafluoroborate to 20 mL of a common high-voltage electrolyte (components: 1.2 M LiPF6 + EC: EMC (v:v = 3:7)) without any additives to obtain a modified electrolyte with a ferrocene tetrafluoroborate concentration of 0.0002 M, and stir at room temperature (about 25°C) for 12 h to completely dissolve it;
[0095] S2: 0.21g of ordinary LiNi without any modification 0.5 Mn 1.5 O4 was mixed with 0.06 g of conductive agent (carbon black SP), 0.6 g of binder (polyvinylidene fluoride PVDF, 5 wt%), and 0.4 g of solvent (N-methylpyrrolidone) as the positive electrode active material, and stirred at room temperature (about 25 ° C) for 2 h to obtain a slurry. The slurry was coated on an Al foil with a 50 μm scraper, and then the coated Al foil was dried in a 110 ° C blast drying oven for 4 h, and then transferred to a vacuum drying oven at 110 ° C for 12 h to obtain LiNi 0.5 Mn 1.5 O4 positive electrode;
[0096] S3: Assemble a half-cell with the lithium sheet as the negative electrode for charge and discharge cycles. First, charge to 4.9V at a rate of 0.2C, then discharge to 3.5V at a rate of 0.2C, and repeat the charge and discharge cycle 5 times at a rate of 0.2C to obtain an in-situ electrochemically modified positive electrode active material, thereby completing the in-situ electrochemical modification of the positive electrode active material.
[0097] Comparative Example 3
[0098] The difference between Comparative Example 3 and Example 1 is that the battery of Comparative Example 3 is not subjected to modification operation.
[0099] Performance Test:
[0100] Figure 1 This is an optical photograph of the modified electrolyte with a ferrocene hexafluorophosphate concentration of 0.0002M prepared in Example 1. Figure 1 It can be seen that ferrocene hexafluorophosphate (C 10 H 10 F6P 10 ) can be completely dissolved in the electrolyte, and the color of the modified electrolyte is light blue.
[0101] Figure 2 The unmodified LiNi used in Example 1 0.5 Mn1.5 The XRD spectrum of O4 is given by Figure 2 It can be seen that the selected positive electrode material LiNi 0.5 Mn 1.5 O4 has a spinel structure, high crystallinity, and its peak position matches well with the XRD standard card, without any stray peaks.
[0102] Figure 3 The unmodified LiNi used in Example 1 0.5 Mn 1.5 SEM image of O4. Figure 3 a and Figure 3 From the b in the figure, we can see that the spinel structure of LiNi 0.5 Mn 1.5 The O4 particles are mainly octahedral in morphology and the particle sizes are uneven.
[0103] Figure 4 The unmodified LiNi used in this Example 1 0.5 Mn 1.5 TEM image of O4, by Figure 4 It can be seen that LiNi 0.5 Mn 1.5 The dominant exposed crystal plane of O4 is the (111) crystal plane.
[0104] Figure 5 The unmodified LiNi used in Example 1 0.5 Mn 1.5 The element distribution picture of O4 material shows that Mn, Ni and O are evenly distributed in LiNi 0.5 Mn 1.5 O4 material.
[0105] The cycle performance of the batteries prepared in the examples and comparative examples was tested according to the following method: the batteries were first charged to 4.9 V at a rate of 0.5 C, then discharged to 3.5 V at a rate of 0.5 C, and this rate was maintained for subsequent cycles to obtain the cycle performance data.
[0106] Figure 6 The following is a graph showing the cycle performance of the lithium-ion batteries prepared in Example 1 and Comparative Example 3. Figure 6 It can be seen that the first discharge capacity of the electrode is 116.2 mAh / g at a discharge current density of 0.5C. After 500 charge and discharge cycles, its discharge capacity remains at 92.4 mAh / g, and the capacity retention rate is 79.52%, revealing that the modified electrolyte can improve the performance of LiNi 0.5 Mn 1.5 Cycling performance of O4 cathode materials.
[0107] Figure 7The figure is a rate performance diagram of the lithium ion battery prepared in Example 1 and Comparative Example 3. Figure 7 It can be seen that the capacity decay of the positive electrode material in the battery of Example 1 of the present invention is not obvious at the discharge current density of 0.2C, 0.5C, 1C, 2C, 5C, 10C, and 20C, and when the discharge current is restored to 0.2C, the capacity can also be restored to the initial value, which shows that the modified electrolyte in the battery of the present invention can improve the LiNi 0.5 Mn 1.5 The rate performance of O4 positive electrode materials is further demonstrated, and the key role of in-situ electrochemical cation doping method in the comprehensive electrochemical performance of lithium-ion batteries is further illustrated.
[0108] Figure 8 For LiNi in Example 1 0.5 Mn 1.5 TEM images of O4 cathode before and after modification. Figure 8 It can be seen that Figure 8 a is unmodified LiNi 0.5 Mn 1.5 The TEM image of the O4 positive electrode shows that the thickness of the CEI layer on its surface is uneven. The maximum thickness is 13.6nm. Moreover, the CEI film does not completely cover the surface of the LNMO particles. It is not uniform and dense enough and appears broken. Figure 8 b is the LiNi modified by battery cycle in Example 1 0.5 Mn 1.5 TEM image of O4 positive electrode, modified LiNi 0.5 Mn 1.5 The thickness of the CEI film on the O4 surface is only 2.5nm. The film layer is dense and uniform and completely covers the surface of the particles. This uniform, dense and complete CEI layer is beneficial to inhibiting the side reactions between the surface of the positive electrode material and the electrolyte, and effectively prevents the dissolution of Mn.
[0109] Fig. 9 For LiNi in Example 1 0.5 Mn 1.5 TOF-SIMS images of O4 positive electrode before and after modification. Fig. 9 a is unmodified LiNi 0.5 Mn 1.5 TOF-SIMS image of O4 positive electrode, where LiF2 - The ions are mainly distributed on the surface of the CEI membrane, indicating that the content of inert components in the CEI membrane is low when it is initially formed, resulting in its poor ability to inhibit side reactions at the cathode / electrolyte interface, which in turn leads to poor stability of the CEI membrane, which is prone to damage and fracture during the process of lithium insertion (volume expansion) / lithium removal (volume reduction) of the LNMO crystal. Fig. 9 b is the LiNi modified by battery cycle in Example 10.5 Mn 1.5 TOF-SIMS image of O4 positive electrode, where LiF2 - The ions are mainly distributed on the surface of the cathode material, indicating that the CEI membrane has a high content of inert components when it is initially formed, which is beneficial to inhibit harmful side reactions at the cathode / electrolyte interface.
[0110] Fig.10 The LiNi modified by battery cycle in Example 1 0.5 Mn 1.5 The element distribution picture of O4 positive electrode shows that Mn, Ni, O, and Fe are evenly distributed in the LiNi after cycling. 0.5 Mn 1.5 O4 material, indicating that Fe 3+ uniform doping.
[0111] Fig.11 The LiNi modified by battery cycle in Example 1 0.5 Mn 1.5 XPS etching picture of Fe element of O4 positive electrode. It can be seen from the figure that Fe peaks can be detected at etching 0s, 30s, 60s, 90s and 120s, indicating uniform doping of Fe ions.
[0112] Fig.12 The following is a graph showing the cycle performance of the lithium-ion batteries prepared in Example 1 and Comparative Example 1. Fig.12 It can be seen that the first discharge capacity of Comparative Example 1 at a discharge current density of 0.5C is 105.5mAh / g. After 350 charge and discharge cycles, its discharge capacity remains at 55.5mAh / g, and the capacity retention rate is 52.6%, revealing that the ferrocene additive in Comparative Example 1 cannot provide the same effect as the ferrocene hexafluorophosphate additive in Example 1.
[0113] Fig.13 The following is a graph showing the cycle performance of the lithium-ion batteries prepared in Example 1 and Comparative Example 2. Fig.13 It can be seen that the first discharge capacity of Comparative Example 2 at a discharge current density of 0.5C is 109.9 mAh / g. After 350 charge and discharge cycles, its discharge capacity remains at 88.3 mAh / g, and the capacity retention rate is 80.3%, revealing that the ferrocene tetrafluoroborate additive in Comparative Example 2 cannot provide the same effect as the ferrocene hexafluorophosphate additive in Example 1.
[0114] The above are only embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent transformations made using the contents of the present invention specification, or directly or indirectly applied in related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. An in-situ electrochemical modification method for a positive electrode active material, characterized in that: The following steps are involved: LiNi 0.5 Mn 1.5 O4 is used as a positive electrode active material to prepare a slurry, the slurry is coated on a metal foil to obtain a slurry layer, and the slurry layer is dried to obtain a positive electrode sheet; The positive electrode sheet, the electrolyte containing ferrocene hexafluorophosphate and the negative electrode are assembled into a battery, and the in-situ electrochemical modification of the positive electrode active material is completed through charge and discharge cycles.
2. The method according to claim 1, characterized in that: The concentration of ferrocene hexafluorophosphate in the electrolyte containing ferrocene hexafluorophosphate is 0.0001M to 0.0005M.
3. The method according to claim 1, characterized in that: The charge-discharge cycle comprises the following steps: firstly charging to 4.9-5.0V at a rate of 0.1C-0.3C, then discharging to 3.5-3.6V at the same rate, and performing 3-5 charge-discharge cycles to obtain an in-situ electrochemically modified positive electrode active material.
4. The method according to claim 1, characterized in that: In the process of preparing the slurry, positive electrode active material, conductive agent and binder are also used, and the mass ratio of the positive electrode active material, conductive agent and binder is 7-9:2-3:
1.
5. The method according to claim 1, characterized in that: The thickness of the slurry layer is 50-200 μm.
6. The method according to claim 1, characterized in that: The drying is a two-step drying process. The first step of drying is to dry the metal foil coated with the slurry at 80°C to 110°C under normal pressure. The second step of drying is to dry the metal foil at 80°C to 110°C under vacuum.
7. The method according to claim 6, characterized in that: The ratio of the first step drying time to the second step drying time is 1 to 4 hours: 8 to 12 hours.
8. The method according to claim 7, characterized in that: The components of the electrolyte include: ferrocene hexafluorophosphate, lithium hexafluorophosphate and a solvent.
9. A positive electrode active material, characterized in that: Prepared by the method according to any one of claims 1 to 8.
10. A lithium ion battery, characterized in that: Comprising the positive electrode active material as claimed in claim 9.
Citation Information
Patent Citations
Electrolyte modifying method for improving cycling stability and low temperature performance of 5V LiNi0.5Mn1.5O4 anode material
CN103219508A
Quasi-solid electrolyte and preparation method thereof
CN103280318A
Electrolyte additive as well as preparation method and application thereof
CN118005543A
Secondary battery
JP1994295726A
Nonaqueous electrolyte secondary battery manufacturing method
JP2013235826A